Maternal and Neonatal Factors Associated with Cerebral Palsy: A Case Control Study At Agona in the Central Region of Ghana - Adomako, I. (University of Ghana, 2017)
Background: Cerebral palsy (CP) refers to multiple, non-progressive, heterogeneous group of syndromes of posture and motor development. It is the most common motor disability in children, with a global prevalence of2-3 per 1000 live births. The prevalence is highest in developing countries, constituting a huge social and economic burden to families and the health system. Maternal and neonatal factors account for about 90-95% of all CP cases. The Objectives: This study sought to determine maternal and neonatal factors and types, and assessed management options of children with cerebral palsy at the Duakwa Rehabilitation centre. Methods: The study used a case-control design, with cases defined as children less than 5 years, born singleton with confirmed diagnosis of CP by a Paediatrician. Controls were Children less than 5 years with a medical condition other than CP. A pretested questionnaire was administered to mothers to obtain information on socio-demographic as well as maternal and neonatal factors associated with CP. The study was conducted at the Salvation Army Rehabilitation centre, Agona Duakwa, in the Central Region. Results: After adjusting for key variables considered in this study, 9 factors were significantly associated with CPo These were: late menarche (adjusted OR=O.OI, 95% CI: 0.002 to 0.84), multiparity (OR=0.47, 95% CI: 0.23 to 0.93), good ANC attendance (OR=0.60, 95% CI: 0.06 to 0.96); constituting the maternal factors. For the neonatal factors, significant associations were found with: Birth asphyxia (OR=20.56, 95% CI: 3.50 to 120.33), Neonatal jaundice (OR=16.30, 950/oCl: 1.66 to 70.88), Neonatal seizures (OR=29.00, 95% CI: 1.55 to 55.67) and Neonatal admissions with an OR of7.32 (95% CI: 1.60 to 33.41). Ethnicity and the locality of the mother were among the demographic factors associated with CP in the study. Conclusion: The study identified 3 main neonatal factors (neonatal seizures, neonatal jaundice and birth asphyxia) which were statistically significantly associated with CP Protective maternal factors in the study included: late menarche, after 14 years, good ANC attendance and multiparity. The two demographic factors; mother's ethnicity and locality, which showed significant association with CP need further studies to confirm this association.
MPH
Keywords: Cerebral palsy (CP); Neonatal Factors; Agona; Central Region; Ghana